Student errors in solving quadratic equations - Daniar Wahyuningtyas; Mutina Mutina; Sukoriyanto Sukoriyanto (State Islamic University of North Sumatra, 2025)
Quadratic equations are fundamental mathematical concepts taught at the junior high school level and are widely used in solving mathematical problems. However, many students still experience difficulties and make errors when solving problems related to quadratic equations. This study aims to examine the types of errors made by students in solving quadratic equation problems. The analysis was conducted by reviewing relevant previous studies selected based on predetermined inclusion and exclusion criteria. Seven articles obtained from Google Scholar were analyzed. The results indicate that students